Manhaj Muktarah Li Tadrîs Al-Kalimãt Al-Malayuwiyyah Dzãtu Ashl Al-‘Arabiy Li At-Thullab Al-Malãyûwiyîn Min Khilãli Qãmus Dãyã - M. Ropi; Mulyadi (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2021)
هدفت هذه الدراسة إلى المعرفة واكتشاف الكلمات الملايوية ذات أصل عربي في قاموس دايا من N إلى S نموذجا، وثانيهما تصميمها إلى منهج مقترح لغرض تسهيل معلمين لتعليم اللغة العربية للملايويين. وكذلك لمعرفتهم على أن بين اللغتين، الملايوية والعربية علاقة قوية منذ دخول الإسلام في أرض ملايو. وهذا البحث يساعد الطلاب على تعلم اللغة العربية بحيث أنهم يدرسون اللغة العربية مستعينين بلغتهم، فيكون التعلم وحفظ المفردات وفهم المعاني أسهل. ولإنجاز هذه الدراسة العلمية يسلك الباحث المنهج النوعي، وذلك من خلال تصميم المنهج المقترح من الكلمات الملاوية ذات أصل عربي لتعليم اللغة العربية للملاويين، بالاعتماد على كتب تعليم اللغة العربية، والاستفادة منها في تعليم اللغة العربية للملايويين. تواصل الباحث إلى هذه الدراسة في النتيجتين؛ أولهما وجود الكلمات ذات أصل عربي في قاموس دايا وعددها بلغ 175 كلمة من حرفN إلى حرف S، وثانيهما أنه من خلال هذه الكلمات الملايوية يمكن تسهيل عملية التعليم والتعلم، ويكون ذلك في تصميم المنهج المناسب لهم،وذلك باستخدام تلك الكلمات التي لها أصل عربي لتعليم اللغة العربية. وتضمنت هذه الدراسة المهارات الأربع، من الحوارات، والمفرادات، والتدريبات، والنصوص، وكذلك الأساليب والطرق في تعليم اللغة العربية للملايويين. This study aims to know and find Malay words derived from Arabic in the DAYA then design it into the proposed curriculum to facilitate the teaching of Arabic to the Malay Community. and also to their knowledge that between the two languages, Malay and Arabic, there has been a strong connection since the introduction of Islam in Malay lands. This research helps students learn Arabic indirectly using their language, so they can learn, memorize vocabulary and understand its meaning more easily. To achieve this scientific study, researchers took a qualitative approach by designing a proposed curriculum of Malay words derived from Arabic for teaching Arabic in Malay communities, by researching Arabic textbooks and using them for teaching Arabic in Malay communities. Researchers found two results: the first is the presence of Arabic words in the Daya dictionary and the number reaches around 184 and the second is through these Malay words, the teaching and learning process can be facilitated in designing a curriculum appropriate for the Malay community, and that is by using the words of Malay Language which originated from Arabic making it easier for Malay people to learn Arabic. This study includes four skills except for writing skills, and in them consists of dialogues, vocabulary, exercises, and texts, as well as methods and methods in teaching Arabic to Malay beginners.